(untitled) (International journal of artificial intelligence, 2025)
In this article, due to violations of the normal movement mode of vehicles on highways, city streets and squares, people are killed, injured, as well as damage to vehicles and their loads, damage to artificial structures on the road. or accidents causing other types of material damage are called traffic accidents.